Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1161/strokeaha.118.023813
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Modafinil-Treatment Response in Poststroke Fatigue Using Brain Morphometry and Functional Connectivity

Abstract: Background and Purpose— Poststroke fatigue affects a large proportion of stroke survivors and is associated with a poor quality of life. In a recent trial, modafinil was shown to be an effective agent in reducing poststroke fatigue; however, not all patients reported a significant decrease in fatigue with therapy. We sought to investigate clinical and radiological predictors of fatigue reduction with modafinil therapy in a stroke survivor cohort. Methods— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…Furthermore, we selected participants that were eligible (MRI safety) and consented to the imaging arm of this study. There were no significant differences in fatigue scores between those participants that were included in the imaging study and those who only participated in the main MIDAS trial 58 .…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, we selected participants that were eligible (MRI safety) and consented to the imaging arm of this study. There were no significant differences in fatigue scores between those participants that were included in the imaging study and those who only participated in the main MIDAS trial 58 .…”
Section: Discussionmentioning
confidence: 83%
“…Most of the interventional studies have a medium to high risk of bias. Table 2 shows only two studies in white cells (indicating low risk of bias) but both have small sample size consisting of 34 (MIDAS study 63 68 ) and 64 randomised patients 61 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Using these techniques, it has been reported that lower global efficiency in an apathy-related subnetwork was an independent risk factor for post-stroke apathy ( 14 ). Recent study showed that functional connectivity of the fronto-striato-thalamic network predicted the response for chronic PSF treatment with modafinil ( 15 ). However, in this study structural connectivity that provide structural basis for the functional interactions between brain regions, was not examined.…”
Section: Introductionmentioning
confidence: 99%